Flexibilidade espacial: um princípio revisitado em empreendimentos imobiliários paulistanos - Machado, Aline Triñanes (2012)
This dissertation presents the way the São Paulo residencial buildings production from the beginning of 21th century has been reproducing the spatial flexibility, which implicates in designs with free and fluid spatiality, rescuing one of the lecorbusierian principles, dear to the modern architecture, allowing programmatic diversity and space singularities. The concept of flexibility has been retaking in the design of a specific real state niche as a way of rescue a benefic quality to your users, but mainly aggregate market value to your buildings, designed as real state products. Thus, there is a necessity to characterize this phenomenon since its begging, both from the technical, spatial and constructible points of view, as the conformation of the condominiums. The investigation of the phenomenon will be based on survey of the theoretical issues involved, the recent reports on the production of the São Paulo real state vertical residencies and the analysis of the flexible apartments plans from the last decade.